Influence knowledge finance attitude finance personality and level education to behavior management finance - Rati Pundissing; Chrismesi Pagiu (Institute of Computer Science (IOCS), 2023)
Knowledge and skills related to public finances are very important for society. The goal is for society to be able to manage and use money as efficiently as possible. With existing knowledge about finance, society expects to own stock education qualified related financial so that capable of taking attitudes and choices decision finance in a wise manner. Study This aim for know Influence Knowledge Finances, Attitude Finances, Personality, and Educational Levels Influence in a manner together to Behavior Management Finance on Perpetrator Business Small Craft weaving in Sa'dan Regency North Toraja. Study This goal is to understand how Knowledge Finances, Attitude Finances, Personality, and Educational Levels Influence Behavior Management Finance on Perpetrator Business Small Craft Weaving in Sa'dan Regency, North Toraja. ny as 57 people. Data collection techniques using a questionnaire Technique analysis Which was used in the study? This is a regression linear double. Research results show that knowledge finance, attitude finance, personality, and level education in a manner together (simultaneously) influence behavior management finance on perpetrator business small craft weaving in Sa'dan Regency, North Toraja.